2019
DOI: 10.1002/pssr.201900025
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Amorphous Cr2O3 Modified Metallic Electrodes for Hydrogen Evolution Reaction

Abstract: The surface modification of benchmarked metal catalysts using nanostructured non‐metallic materials for improved performance and stability is an active area of research and is interesting from both a fundamental and an applied perspective. Amorphous few layered nanosheets of Cr2O3 (3–5 nm) are synthesized by rapid thermal exfoliation of CrCl3 · 6H2O precursors and are characterized. The hydrogen evolution reaction (HER) studies on alkaline medium conducted with platinum and gold electrodes modified with amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…The O v content in the CrO x ‐Ni 3 N samples is larger than that in Ni 3 N and is gradually increased along with the increasing CrO x . the Raman spectra (Figure S14a, Supporting Information) for the amorphous CrO x show a similar shape with the crystalline Cr 2 O 3 , [ 23 ] but a shift from 542 to 538 cm −1 is attributed to the generation of oxygen vacancies in amorphous CrO x . Two fairly weak peaks at 512 and 732 cm −1 in Ni 3 N (Figure S14b, Supporting Information) correspond to the formation of NiO bond by the surface oxidation of Ni 3 N. [ 24 ] The Raman spectrum of the CrO x ‐Ni 3 N mainly contains two broad peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The O v content in the CrO x ‐Ni 3 N samples is larger than that in Ni 3 N and is gradually increased along with the increasing CrO x . the Raman spectra (Figure S14a, Supporting Information) for the amorphous CrO x show a similar shape with the crystalline Cr 2 O 3 , [ 23 ] but a shift from 542 to 538 cm −1 is attributed to the generation of oxygen vacancies in amorphous CrO x . Two fairly weak peaks at 512 and 732 cm −1 in Ni 3 N (Figure S14b, Supporting Information) correspond to the formation of NiO bond by the surface oxidation of Ni 3 N. [ 24 ] The Raman spectrum of the CrO x ‐Ni 3 N mainly contains two broad peaks.…”
Section: Resultsmentioning
confidence: 99%
“…In order to confirm whether the Pt counter electrode can influence on HER performance, we performed LSV polarization curves for HER in 0.1 M KOH solution using bare GCE (glassy carbon electrode) as the working electrode and Pt foil and/or graphite rod as the counter electrode . Figure S11A compares the HER performance of GCE working electrode when graphite rod or Pt foil is separately used as the counter electrode.…”
Section: Electrochemical Studiesmentioning
confidence: 87%
“…The EIS spectra of all electrodes were in tune with the LSV measurements, demonstrating the enhanced charge transfer and augmented HER activity on Ni/Cr 2 O 3 /PGE electrodes compared with their individual electrodes. Previous studies have reported that 3d-metal oxides and/or oxyhydroxides improved catalysis toward the splitting of water. , Indeed, when comparing the results obtained for Ni/PGE, Cr 2 O 3 /PGE, and Ni/Cr 2 O 3 /PGE, the role of Cr 2 O 3 can be explained based on this observation. According to these studies, the splitting of water into H + and OH – occurs on the Cr 2 O 3 surface, providing a large supply of protons for the process of H + reduction.…”
Section: Resultsmentioning
confidence: 60%
“…Chromium­(III) oxide (Cr 2 O 3 ), the most stable oxide of chromium, naturally occurs as eskolaite mineral . Cr 2 O 3 is a rigid and fragile material that has a hexagonal crystal structure, which has been used in many applications, such as lithium-ion batteries, supercapacitors, gas sensors, and magnetoelectric data storage. Several studies have shown that Cr 2 O 3 exhibits high electrocatalytic activity and long-term stability for HER. According to previous reports, nanostructured Cr 2 O 3 materials are prepared using various methods, such as chemical vapor deposition, the sol–gel method, physical vapor deposition, the microwave oven method, electrostatic spray deposition, and the precipitation technique. , The electrochemical technique, among other applications, is advantageous because it is inexpensive, straightforward, and applicable under ambient conditions. No studies have reported on the electrochemical synthesis of Cr 2 O 3 nanostructures directly on the electrode surface via potentiometric deposition using a three-electrode cell system.…”
Section: Introductionmentioning
confidence: 99%